Ecological studies on brown bear (Ursus arctos) in Belarus: distribution, population trends and dietary structure - Sidorovič, Vadim Evgenevich (2006)
The goal of the study was to get knowledge about the current distribution and population trends of brown bear (Ursus arctos) in Belarus. Another aim was to analyse the dietary composition of the species on a seasonal basis. The main methods used were track survey and scat investigation. The study suggests that in Belarus brown bears occur mostly in northern and central-eastern districts. One of the population trends was increase in predator numbers in north-eastern and central-eastern districts, whereas another population trend was a gradual decline in brown bears in north-western districts. The total number of brown bears in Belarus was approximately between 140 and 180 (plausibly 160) individuals in 2002-2003. A markedly lower number of brown bears was recorded in 2005 and the data obtained suggest a decreased number of up to 80-100 individuals during the last years. According to the data on the dietary composition of brown bear in northern Belarus, the species may be characterised as a generalist and rather a plant consumer than an active predator. Insects and carrion also play an important role in the feeding of brown bear.